The Lesson Activities Map: A Domain-Specific Lesson Transcription Methodology - Annamaria Savona* (European Journal of Educational Research, 2021)
In educational research, audio-video recordings allow observing a lesson repeatedly. The collected data needs to be transcribed for analysis. Although methodologies for transcribing video-recorded lessons are established, there is lack of transcription methodologies for certain types of lessons, such as in arts education or the teaching to create new products. In our research project, we examine the teaching–learning of songs in class. Because of the absence of suitable transcription methodologies, we developed a new systematic approach. This paper presents the Lesson Activities Map (LAMap), which consists of symbols and icons representing graphically the constitutive elements of a domain-specific lesson. As a result, the LAMap provides a visualisation of the lesson content – in this context the song – and of how a teacher works on parts and the whole. The graphic representation supports the lesson analysis from different perspectives. The LAMap methodology and applications are valuable for transcribing other subject-specific lessons.